2003
DOI: 10.1034/j.1399-3089.2003.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate for immunosuppression in life‐supporting pig‐to‐cynomolgus monkey renal xenotransplantation

Abstract: Methotrexate (MTX) has been used successfully as an immunosuppressant in rodent xenotransplantation models, but the data generated so far with MTX in pig-to-baboon cardiac transplantation studies have been disappointing. The potential of this agent was consequently explored in a life-supporting pig-to-primate renal model using the cynomolgus monkey as the recipient species. Introductory in vitro and in vivo pharmacokinetic and pharmacodynamic studies with MTX were conducted in three cynomolgus monkeys. Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In all cases, an immunosuppressive regimen consisting of a brief induction followed by a maintenance therapy was Laboratory Animals (2007) 41 administered peri-and postoperatively to prevent or delay the onset of the rejection process (Cozzi et al 2003a(Cozzi et al , 2004. All xenograft recipients were given an induction immunosuppressive regimen consisting of up to four doses of cyclophosphamide (Endoxan s ; Baxter, Milan, Italy), cyclosporin A (Neoral s ; Novartis Pharma AG, Basel, Switzerland) administered orally twice a day, adjusted individually to maintain a 12 h blood trough concentration of 300-600 ng/mL, and GAS914 (Novartis Pharma AG), an injectable polymer expressing the carbohydrate moieties Gala1-3Galb1-4Glc-Nac-R (Katopodis et al 2002) The primate recipients of life-supporting renal xenografts at our centre survived for up to 90 days (range 1-90 days; mean 21.3716.9 days; median 16 days; mean creatinine level at the time of euthanasia was 6507 300 mmol/L).…”
Section: The Animal Modelmentioning
confidence: 99%
“…In all cases, an immunosuppressive regimen consisting of a brief induction followed by a maintenance therapy was Laboratory Animals (2007) 41 administered peri-and postoperatively to prevent or delay the onset of the rejection process (Cozzi et al 2003a(Cozzi et al , 2004. All xenograft recipients were given an induction immunosuppressive regimen consisting of up to four doses of cyclophosphamide (Endoxan s ; Baxter, Milan, Italy), cyclosporin A (Neoral s ; Novartis Pharma AG, Basel, Switzerland) administered orally twice a day, adjusted individually to maintain a 12 h blood trough concentration of 300-600 ng/mL, and GAS914 (Novartis Pharma AG), an injectable polymer expressing the carbohydrate moieties Gala1-3Galb1-4Glc-Nac-R (Katopodis et al 2002) The primate recipients of life-supporting renal xenografts at our centre survived for up to 90 days (range 1-90 days; mean 21.3716.9 days; median 16 days; mean creatinine level at the time of euthanasia was 6507 300 mmol/L).…”
Section: The Animal Modelmentioning
confidence: 99%
“…Recent work from our laboratory has demonstrated that various degrees of compensated consumptive coagulopathy may indeed occur in the pig-to-cynomolgus monkey model (5), but neither we (5,6) nor several other authors (7)(8)(9)(10)(11)(12) were able to confirm the high prevalence of DIC reported elsewhere (1,3,4,13), even when baboons were used as the recipient species (11,12). On the other hand, there is no doubting that, irrespective of the vascularized organ transplanted or the recipient species considered, fibrin deposition is a consistent finding in organs damaged by acute humoral xenograft rejection (AHXR) (14).…”
mentioning
confidence: 70%
“…The surgical procedure and the immunosuppression used have been described in detail elsewhere (6,10). Briefly, each primate was given immunosuppression consisting of up to 4 doses of cyclophosphamide iv.…”
Section: Renal Xenotransplantationmentioning
confidence: 99%
“…), when transplanted into primates, organs from transgenic pigs expressing human CD55, in the large majority of cases, are not subject to HAR. However, these organs eventually fail due to AHXR [16] in the presence of C3b and C5b-9 deposition, possibly indicating the inappropriate downregulation of the complement cascade as a contributing factor [43,197,198]. In support of such an hypothesis, C3 and MAC were still detected on hDAF transgenic cells exposed in vitro to human complement, although greatly reduced [199].…”
Section: Interference With the Activation Of The Complement Cascadementioning
confidence: 99%
“…As far as induction regimens are concerned, these have included short term treatments with cyclophosphamide, metothrexate, mitoxantrone and polyclonal or monoclonal anti-lymphocyte antibodies [78,197,198,203,[207][208][209][210]. Maintenance immunosuppression has also relied on the use of both well characterized or recently developed immunosuppressants that include tacrolimus [78,211], FTY720 [210], SDZ-RAD [47], mycophenolic acid [78,197,198,203,205,208,212,213] and deoxyspergualin [212].…”
Section: Conventional Drugs and Other Immunosuppressantsmentioning
confidence: 99%